Question and Answer service decentralised: PRAIS is right - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
CTA has decided to decentralise its long-established question and answer (Q&A) service to a number of regional centres. Preliminary consultations are underway in the Caribbean (CARDI for Trinidad and Tobago, and Jamaica and Saint Lucia) and East...